Resilience in Higher Education: Coping with Change and Disruptions through Biographical Narratives - Orozco Castro , Cynthia (2025)
This article, developed using a qualitative methodology of biographical reconstruction, describes the coping mechanisms and resources employed by university students to adapt to disruptive events. The research focused on two adjustment periods at the Western Campus of the University of Costa Rica: the move into student residences and the virtualization of academic processes during the COVID-19 pandemic. It also incorporates the perspective of Student Life (SL) staff, establishing a balance between the perceptions of young people and those of adults. The results demonstrate that systematic daily actions and contextual (ecosystemic) support are fundamental for building resilience in the medium and long term. The importance of quality relationships and perceived social support as protective factors is highlighted. Two types of support were identified: formal resilience mentors, such as SL staff and services, who offered organized support, institutional resources, and cognitive restructuring strategies in the face of the crisis; and informal resilience mentors (friends, classmates, and family members), whose role was essential in providing emotional support and empathy in daily life. The study concludes that the early establishment of successful connections with the university, along with the integration of formal and informal resources, constitutes a set of key protective factors for building long-term resilience and student retention.